Promoter‐pervasive transcription causes RNA polymerase II pausing to boost DOG1 expression in response to salt. (27th January 2023) - Montez, Miguel; Majchrowska, Maria; Krzyszton, Michal; Bokota, Grzegorz; Sacharowski, Sebastian; Wrona, Magdalena; Yatusevich, Ruslan; Massana, Ferran; Plewczynski, Dariusz; Swiezewski, Szymon
Abstract: Eukaryotic genomes are pervasively transcribed by RNA polymerase II. Yet, the molecular and biological implications of such a phenomenon are still largely puzzling. Here, we describe noncoding RNA transcription upstream of the Arabidopsis thaliana DOG1 gene, which governs salt stress responses and is a key regulator of seed dormancy. We find that expression of the DOG1 gene is induced by salt stress, thereby causing a delay in seed germination. We uncover extensive transcriptional activity on the promoter of the DOG1 gene, which produces a variety of lncRNAs. These lncRNAs, named PUPPIES, are co‐directionally transcribed and extend into the DOG1 coding region. We show that PUPPIES RNAs respond to salt stress and boost DOG1 expression, resulting in delayed germination. This positive role of pervasive PUPPIES transcription on DOG1 gene expression is associated with augmented pausing of RNA polymerase II, slower transcription and higher transcriptional burst size. These findings highlight the positive role of upstream co‐directional transcription in controlling transcriptional dynamics of downstream genes. Synopsis: DOG1 is a key regulator of plant seed dormancy, whose expression is regulated by multiple mechanisms. Here, salt stress is found to induce pervasive lncRNA transcription within the DOG1 promoter region, resulting in augmented RNA Polymerase II pausing, slower transcription and increased DOG1 expression. The DOG1 gene restricts seed germination under salt stress independently of its function in primary dormancy. The DOG1 promoter region gives rise to salt stress‐responsive PUPPIES lncRNAs, which regulate DOG1 expression in cis to delay germination. Co‐directional pervasive transcription of PUPPIES activates DOG1 expression through augmented RNA polymerase II pausing and enhanced transcriptional bursting. The identified regulatory mechanism involves an increase of RNA molecules produced per DOG1 transcriptional burst, augmented pausing and slower transcription. Abstract : PUPPIES lncRNAs transcription from the promoter of seed dormancy regulator DOG1 augments pausing of RNA polymerase II and delays germination.